Solvent-based formulations for intravenous mouse pharmacokinetic studies: tolerability and recommended solvent dose limits. (March 2014) - Thackaberry, Evan A.; Wang, Xiaojing; Schweiger, Michelle; Messick, Kirsten; Valle, Nicole; Dean, Brian; Sambrone, Amy; Bowman, Terri; Xie, Minli
Abstract 1. Modern high-throughput small molecule drug discovery requires rapid screening of the pharmacokinetic parameters of multiple candidate molecules in parallel. The mouse is often used for such screening, as are solvent-based intravenous formulations. Despite this, the intravenous toxicity of many commonly used solvents is unknown. The purpose of this investigation is to establish recommended no-observed-effect level (NOEL) and maximum tolerated dose (MTD) for several commonly used intravenous solvents in the CD-1 mouse. 2. The acute tolerability of polyethylene glycol 400, N-methylpyrrolidone, dimethyl sulfoxide, ethanol, dimethylacetamide and propylene glycol was established, along with combinations of polyethylene glycol 400 and/or ethanol and DMSO. Based on these data, an acute NOEL and recommended MTD is reported for each solvent or solvent combination. 3. These data can guide the use of these solvents to support single-dose intravenous pharmacokinetic studies in mice. By establishing a defined dose tolerability range for the most commonly used intravenous solvents, undue pain and distress in animals can be avoided while maximizing the generation of critical pharmacokinetic data for project teams.